Quality Adaptive Online Double Auction in Participatory Sensing - Mukhopadhyay, Jaya; Singh, Vikash Kumar; Mishra, Sachchida Nand; Mukhopadhyay, Sajal; Pal, Anita (Journal of Informatics and Mathematical Sciences, 2017)
Agents (specially humans) with smart devices are stemming with astounding rapidity and that may play a big role in information and communication technology apart from being used only as a mere calling devices. Inculcating the power of smart devices carried by the agents in several different applications is commonly termed as participatory sensing (PS). In this paper, a quality adaptive participatory sensing mechanism is presented in an online double auction environment. The proposed algorithm is simulated with a benchmark mechanism that adapts the existing McAfee’s Double Auction (MDA) directly in the online environment.